Giving up to Gain: Towards the Benchmarks of the “Post-Bologna” Development of Higher Education in Russia - K. G. Tkhagapsoev; M. M. Yakhutlov (Высшее образование в России)
The article focuses on the strategies and mechanisms for the development of higher education practiced in modern Russia. They are analyzed in terms of their effectiveness and adequacy to the needs of the country’s development. The authors emphasize the inertial predominance of the ideological impulses of radical liberalism of the 1990s in these strategies, including managerialism. The article raises the question about the need to adjust the general course, goals and mechanisms for the development of domestic higher education, taking into account the pressing challenges to the country and education, the features of the current stage of Russia’s development. The authors propose the concrete measures in this direction. At the same time, special attention is paid to the differentiation of strategies for the development of educational institutions, increasing the role of democratic mechanisms in the life of the university and in the management of the university.